2021
DOI: 10.1016/s1470-2045(21)00027-9
|View full text |Cite
|
Sign up to set email alerts
|

Second-line FOLFOX chemotherapy versus active symptom control for advanced biliary tract cancer (ABC-06): a phase 3, open-label, randomised, controlled trial

Abstract: Background Advanced biliary tract cancer has a poor prognosis. Cisplatin and gemcitabine is the standard first-line chemotherapy regimen, but no robust evidence is available for second-line chemotherapy. The aim of this study was to determine the benefit derived from second-line FOLFOX (folinic acid, fluorouracil, and oxaliplatin) chemotherapy in advanced biliary tract cancer. MethodsThe ABC-06 clinical trial was a phase 3, open-label, randomised trial done in 20 sites with expertise in managing biliary tract … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
422
3
18

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 501 publications
(455 citation statements)
references
References 36 publications
12
422
3
18
Order By: Relevance
“…In contrast to ablation, results of EBRT and IAT suffered from high heterogeneity of the results and unclear superiority of outcomes, as compared with what could be expected from systemic chemotherapy in liver-only iCC (pooled objective response rates of 23.4% to 41.3%; and pooled mean OS ranging between 14.1 and 21.3 months with wide CIs). These results do not allow for strong recommendations, especially in the context of the efficacy demonstrated in phase III trials with systemic chemotherapy [3,12]. Comparison of efficacy between the three IAT modalities would prove difficult as the populations included differed.…”
Section: Discussionmentioning
confidence: 95%
“…In contrast to ablation, results of EBRT and IAT suffered from high heterogeneity of the results and unclear superiority of outcomes, as compared with what could be expected from systemic chemotherapy in liver-only iCC (pooled objective response rates of 23.4% to 41.3%; and pooled mean OS ranging between 14.1 and 21.3 months with wide CIs). These results do not allow for strong recommendations, especially in the context of the efficacy demonstrated in phase III trials with systemic chemotherapy [3,12]. Comparison of efficacy between the three IAT modalities would prove difficult as the populations included differed.…”
Section: Discussionmentioning
confidence: 95%
“…Recently, emerging outputs from the multiple phase II trials demonstrated that fluoropyrimidine-based chemotherapy, considered as the second-line treatment, benefited patients with advanced cholangiocarcinoma refractory to first-line chemotherapy (19). In recent ABC-06 trial, second-line mFOLFOX (folinic acid, 5-fluorouracil, and oxaliplatin) plus active symptom control (ASC) improved OS compared with ASC alone (12 months versus 6 months), providing evidence for the promising survival benefits of the use of second-line chemotherapy after progression on the cisplatin-gemcitabine combination (mFOLFOX+ASC versus ASC: HR 0.69, 95% CI 0.50-0.97, P = 0.031) (20).…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, detecting actionable targets though theragnostic biomarkers is highly valuable in BTC: (1) the therapeutic arsenal of advanced BTC is limited in second line [ 172 ] with FOLFOX chemotherapy regimen. This only therapeutic second-line validated to date in a randomized Phase III trial, showed a very modest benefit over best supportive care, with a median OS of 6 months (one month OS gain in OS) and an ORR of 5% [ 31 ] overall responses, including long-lasting responses and/or complete responses, are frequent with IDH1/2 and FGFR2 inhibitors; (2) most molecular profiling panels would also detect rare targets, such as NTRK fusions, interesting since NTRK inhibitors are approved regardless of the tumor type, or other rare fusion genes for which clinical trials are available; (3) besides tumors with known prevalent oncogenic driver such as gastro-intestinal stromal tumor (GIST, c-kit mutations) or melanoma (BRAF mutations), BTC are among the tumors with one of the highest frequency of actionable molecular alterations. Therefore, molecular screening with NGS is becoming a standard of care for BTC; (4) even if looking for IDH1 and/or FGFR fusion is more relevant in iCCA, NGS allows an identification of several potential actionable targets and it is interesting to be performed regardless of primary tumor localization (e.g., EGFR and HER2 in eCCA and GBC); (5) in addition to solid tissue biopsies, the place of ‘liquid biopsies’ (ctDNA), allowing repeated molecular profiling in a less invasive way, still needs to be validated in BTC.…”
Section: What Is Useful In Clinical Practice?mentioning
confidence: 99%
“…No predictive biomarkers are used yet to select patients for antiangiogenic therapy in HCC with the exception of AFP level for ramucirumab. For BTC, first-line standard chemotherapy is cisplatine-gemcitabine regimen with a median OS of 11.7 months [ 30 ] and in second line, a combination of 5-fluorouracil and oxaliplatine can be proposed [ 31 ]. The poor results obtained with systemic chemotherapy in BTC stress a need for efficient targeted therapies and the need for molecular profiling.…”
Section: Introductionmentioning
confidence: 99%